Enhancement of coal briquette quality through corn stalk blending and binder optimization. Issue 2 (11th September 2014) - Lu, Guangjun; Cheng, Fangqin; Li, Jianfeng
Abstract : In this study, corn stalk was proposed to enhance the quality of coal briquette. The corn stalks were treated with sodium hydroxide solution to generate effective binding agents before mixing with coal fines. Results showed that bio‐coal briquette compressive and falling strength increased with the increase of corn stalk weight ratio. However, the newly formed bio‐coal briquettes were easily broken up when contacted with water. It was found that the bio‐coal briquettes were stable in water for 24 h after polyvinyl alcohol (PVA) including in the binder, and both compressive and falling strength were further increased up to 3.33 MPa and 99.2%, respectively. Redrying compressive strength was about 1.37 MPa, which was independent on corn stalk ratio. It was also demonstrated that oneset temperature, ignition temperature, burnout temperature, and combustion residue decreased as the corn stalk ratio increased with the presence of PVA. This study showed that corn stalk blending was a promising approach to enhance the coal briquette quality. © 2014 American Institute of Chemical Engineers Environ Prog, 34: 613–618, 2015